Exploring the Lecturers’ Perspectives on Their Digital Competence in ELT in Higher Education - Rahmi Fhonna (English Education Journal: Jurnal Pengembangan Pendidikan dan Pengembangan Pengajaran Bahasa, 2025)
In the evolving landscape of higher education, digital competence has become essential for effective teaching, particularly in English language instruction. This research explores the perceptions, practices, and challenges experienced by English lecturers in integrating digital tools into their teaching at the university level. Utilizing a qualitative approach, data were collected through semi-structured interviews with eight English lecturers at Department of English Education, Teacher Training and Tarbiyah Faculty, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia. Guided by the DigCompEdu framework, thematic analysis revealed six major themes: (1) limited understanding of digital competence frameworks; (2) routine use of basic digital tools with minimal pedagogical depth; (3) shifts in teaching norms due to digital adoption; (4) barriers including lack of training and infrastructure; (5) self-directed learning efforts; and (6) a need for structured institutional support. While lecturers demonstrated willingness and initiative to engage with technology, the integration often lacked pedagogical grounding. The findings highlight the urgent need for discipline-specific digital training and policy interventions to support educators in advancing their digital competence in English language teaching (ELT). This research is expected to contribute to the growing discourse on digital readiness in higher education, offering localized insights into teacher development in ELT.